INTERPRETATION OF THE ISSUES OF YOUTH EDUCATION IN THE WORKS OF EASTERN SCHOLARS (Conference Zone, 2022)
In this article, the issue of child upbringing in Uzbek families, Eastern thinkers in child upbringing Muhammad ibn Musa al-Khorazmi, Abu Nasr Farabi, Abu Rayhan Beruni, Abu Ali ibn Sina, Muhammad Kashghari, Yusuf Khos Khajib, Kaikovus, Omar Khayyam, Ahmad Yugnaki , information on the issues of raising children in the family in a number of works of thinkers such as Husayn Vaiz Koshifi.